Enzymes as Potencial Source for Clean Label Bakery Product: Part 2, Mechanism, Application and Optimization Combination Enzymes - Evita Riviani Achmadi (Journal of Food and Agricultural Product, 2022)
Background: Food enzyme is important ingredient for bakery industry to improve production process, functional properties and characteristic bakery product. Food enzym can be applied as single or combination enzym based on purpose which is need on processing. Based on several literatures, application combination enzymes more effective than single enzym, due to synergism effect between enzym which combine. Combination enzymes can be mixed from same or different class of enzym, it is depended on selected specification and characteristic enzym. Application of combination enzymes commonly act as processing aid which added in flour while mixing process. Therefore, it is important to understand work mechanism of combination enzym in processing stage especially mixing, fermentation and baking. Sinergysm in combination enzym can be enhance using optimization method to improve quality of processing and bakery product. Response Surface Methode (RSM) with Central Composite Design (CCD) as a design experiment is the most effective and efficient method which commonly applied for modelling and optimization in food processing. This method helps to make informed decision on a process with the objective of improving efficiency and minimizing cost while maintaining quality.Scope and approach: This review explain about the role combination enzyme application in bakery product which discuss under four main headings include (i) Application of combination enzymes in bakery product ii) Mechanism combination enzymes to enhance bakery product quality include processing (mixing, fermentation and baking) and sensory properties (texture, taste, colour and appearance) iii) Optimization of combination enzym in bakery product using Respond Surface Method (RSM) iv) Regulation food enzym usage in United State, Europian Union and Indonesia. Evaluation mechanism, application and optimization of combination enzymes can be used as a base for sustainable development bakery product which is safe for consume and accordance to food regulation. The differences regulation between country can be considerate when supply and distribution chain of industrial and retail food companies stretch around the globe.Key findings and conclusion: The combination of enzymes provides a synergistic effect depending on the type and mechanism enzymes which is affected each other. Type and mechanism enzymes can be affected with process parameter and ingredient which is a part of food matrix while processing runs. Therefore, the suitability between process parameters, ingredient, specifications and characteristics enzyme are needed to gives significant results for optimization of enzyme combinations in bakery production. Understanding the role of enzymes as a part of food system is important as a basic knowledge in selection of enzymes to be combined. This helps researchers and developers to optimize the combination of enzymes by taking into account conditions of the process stages in bakery production. RSM with CCD as design experiments is the most efficient method because its only requires a small amount runs. CCD uses the build-up principle to build a quadratic model using the information gathered from the 2n factorial design. If the linear model of the 2n factorial is not significant, it is possible to design another trial based on the CCD principle to improve the model. Model improvement using build-up principle is suitable with the food industry needed, which requires fast, precise and accurate validation and verification in making decisions in terms of product development and production process.Keyword: Combination enzymes, RSM (Response Surface Method), CCD (Central Composite    Design), regulation, mechanism, application.